(untitled) (Dhaka University Journal of Biological Sciences, 2025)
The present study investigated the effects of probiotic supplementation on the growth performance and immunity of Nile tilapia (Oreochromis niloticus). A commercial probiotic was incorporated into the feed at 10 g/kg and administered for one month. After this period, significantly higher weight gain and specific growth rate were found in fish receiving the probiotic supplemented diet than fish fed with control diet (p < 0.05). Haematological parameters were also examined, whereby day 7, significantly increased concentration of haemoglobin was found in fish given probiotic supplemented diet than that of fish given control diet (p < 0.05). Moreover, white blood cell (WBC), red blood cell (RBC), and platelet counts were also increased significantly in fish given probiotics in their diet than fish fed diet without probiotics (p < 0.05). However, at day 30, significantly higher count of WBC was found in probiotic supplemented fish than fish fed diet without probiotic (p < 0.05). Furthermore, the probiotic supplemented group of Nile tilapia exhibited significantly elevated expression levels of immune genes including receptor molecules (TLR2, TLR3, TLR8 and TLR9) and effector molecules including IRF3, IL-1β, IL-10, and viperin in the spleen, liver, gill, and brain at 24, 48, and 72 hours of probiotic supplementation (p < 0.05). The findings suggest that dietary probiotics can effectively enhance both growth and immunity in Nile tilapia. Dhaka Univ. J. Biol. Sci. 34(2): 149-162, 2025 (July)